Administrasi Keimigrasian dalam Pengawasan Orang Asing: Telaah Literatur atas Kebijakan dan Pelaksanaannya - Andi Ilyas Sugianto; Arief Febrianto; Imma Yedida Ardi (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study aims to examine immigration administration within the context of foreigner surveillance in Indonesia through a literature review approach. The primary focus is on policy analysis, implementation, challenges, and the effectiveness of surveillance systems based on legal documents, institutional reports, and recent academic publications. Findings indicate that Indonesia’s immigration policy has a relatively strong legal framework through Law No. 6 of 2011 and its derivative regulations. However, its implementation still faces challenges such as limited human resources, uneven technological infrastructure, and suboptimal inter-agency coordination. The adoption of information technology tools such as SIMKIM, APOA, and CEKAL represents an important innovation, although they have not been fully optimized. This study recommends strengthening institutional capacity, updating evidence-based regulations, and enhancing multi-actor collaboration as strategic future steps.